STRATEGI PRE-CLASS QUIZ UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V di SD NEGERI 2 KARANGLUHUR KERTEK WONOSOBO - Fatichatun Najichah; Hidayatu Munawaroh; Nugroho Prasetya Adi (STKIP Subang, 2026)
This study aims to determine the effect of the Pre-Class Quiz strategy on science and social studies (IPAS) learning outcomes of fifth-grade students at SD Negeri 2 Karangluhur Kertek Wonosobo and to measure the magnitude of its effect. This study employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The research sample consisted of 30 fifth-grade students. Data were collected through tests, observations, and documentation. The research instrument was a multiple-choice test that had been validated and tested for reliability. Data analysis included validity testing, reliability testing, normality testing, homogeneity testing, hypothesis testing using the Wilcoxon Signed Rank Test, and effect size analysis. The results showed that the pretest and posttest data were not normally distributed, with significance values of 0.015 and 0.002, respectively. Therefore, hypothesis testing was conducted using the Wilcoxon Signed Rank Test. The analysis produced an Asymp. Sig. (2-tailed) value of 0.000 (<0.05), indicating a significant effect of the Pre-Class Quiz strategy on students’ learning outcomes. Furthermore, the effect size value was 0.83, which falls into the large category. These findings indicate that the Pre-Class Quiz strategy significantly improves students’ learning outcomes and can be effectively implemented in elementary school IPAS learning.